Self‐Blockade of PD‐L1 with Bacteria‐Derived Outer‐Membrane Vesicle for Enhanced Cancer Immunotherapy. Issue 7 (11th January 2022) - Pan, Jingmei; Li, Xilin; Shao, Binfen; Xu, Funeng; Huang, Xuehui; Guo, Xing; Zhou, Shaobing
Abstract: The checkpoint inhibitor therapy that blocks programmed death‐1 (PD‐1) and its major ligand PD‐L1 has achieved encouraging clinical efficacy in certain cancers. However, the binding of checkpoint inhibitors with other immune cells that express PD‐L1 often results in a low response rate to the blockade and severe adverse effects. Herein, an LyP1 polypeptide‐modified outer‐membrane vesicle (LOMV) loaded with a PD‐1 plasmid is developed to achieve self‐blockade of PD‐L1 in tumor cells. The nanocarriers accumulate in the tumor tissue through OMV‐targeting ability and are internalized into the tumor cells via the LyP1‐mediated target, subsequently delivering PD‐1 plasmid into the nucleus, leading to the expression of PD‐1 by the tumor cells. In addition, a magnetic particle chemiluminescence kit is developed to quantitatively detect the binding rate of PD‐1/PD‐L1. The self‐expressed PD‐1 bonded with the PD‐L1 is expressed by both autologous and neighboring tumor cells, achieving self‐blockade. Simultaneously, the outer‐membrane protein of LOMV recruits cytotoxic lymphocyte cells and natural killer cells to tumor tissues and stimulates them to secrete IFN‐γ , improving the antitumor activity of the PD‐1/PD‐L1 self‐blocking therapy. Abstract : An LyP1 polypeptide‐modified outer‐membrane vesicle loaded with a PD‐1 plasmid is developed for inducing the self‐expression of PD‐1 by tumor cells and achieving self‐blockade of the PD‐1/PD‐L1 pathway. The outer‐membrane protein component can recruit cytotoxic lymphocyte cells and natural killer cells to tumor microenvironment, further improving the antitumor activity of the PD‐1/PD‐L1 self‐blocking therapy.